PENTINGNYA PENDIDIKAN KARAKTER DALAM MENGHADAPI ERA GLOBALISASI DI SD NEGERI MUKTIHARJO KIDUL 03 SEMARANG - Urfi Mutiarohmah Hanggraeni Putri; Ikha Listyarini; Suyoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted to determine the importance of character education in facing the era of globalization at SD Negeri Muktiharjo Kidul 03 . By looking at the rapid development of the times, many children lack good social and moral behavior in society. Character education is currently needed to form the next generation of a nation that is qualified, has a Pancasila spirit, and is responsible for facing the era of globalization. The character education of students in elementary schools is the beginning of instilling the character of students, in elementary schools students are in the developmental stage, curiosity and wanting to try or follow it is very high. So because of that the teacher's role is very necessary in the formation of the character of students who are carried out through the process of teaching and learning activities in the classroom. With learning in class, teachers can form good character education directly to their students while at school. In an effort to face the era of globalization that is developing so rapidly, character education is needed to become a self-foundation of the planned and measurable impacts of the globalization era from the government through education. Compared to neighboring countries, education in Indonesia is far behind, because education in Indonesia prioritizes mastery of scientific aspects, intelligence, and pays little attention to aspects of character education. The conclusions obtained by students will know the good and bad of the era of globalization and hope that generations of children of the nation who have a Pancasila spirit will be able to advance the Indonesian nation by implementing character education from an early age.